EFFECT OF EXOGENOUS INDOLE-3-BUTYRIC ACID AND INDOLE-3-ACETIC ACID ON BIOMASS AND LEGENDARY WITHANOLIDES FROM IN VITRO ROOT CULTURES OF WITHANIA SOMNIFERA – JAWAHAR 20 CULTIVAR - PANKAJAVALLI. T; KALAISELVI. R; PRADEEPA.D; KALAISELVI SENTHIL (International Journal of Pharma and Bio Sciences, 2014)
“Withanolides”, the legendary bioactive metabolite present in leaves and roots of Withania somnifera, is well known for its therapeutic activities since ancient times. Several efforts have been made to produce these metabolites under in vitro condition. In the present study, we have tested the effects of exogenous supplementation of IBA and IAA in W. somnifera in vitro root cultures with the aim of optimizing the production of biomass and major withanolides. Among the two auxins, IBA is an effective inducer of lateral root formation thereby increasing the biomass. Accumulation of withanolide A and the biomass increases as the concentration of IBA increased to 1mg/L (2576±0.37 µg/g DW and 12.89±0.25 g/dL respectively). IAA at lower concentration favours relatively high accumulation of withanolide A (1147±0.77 µg/g DW) and at higher concentration of 1mg/L helps in higher accumulation of withaferin A (624±0.87 µg/g DW).